Utilization of MQTT and Radio GPS in Pet Monitoring - Lindawati, Lindawati; Sarjana, Sarjana; Agatha, Adelia (Universitas Negeri Padang, 2024)
This research presents an effective and efficient solution for tracking pets using Message Queuing Telemetry Transport (MQTT) based on radio GPS. The study creates a device and application capable of monitoring the whereabouts of pets to prevent their loss by displaying the latitude and longitude of the pet's location. This application provides real-time monitoring and exhibits high accuracy, with minimal differences in latitude and longitude compared to both animal tracking applications and Google Maps. The application's update speed is also impressive, with a delay of only 4.25 seconds. By continuously developing and enhancing this technology, it is expected to provide broader benefits to the pet-loving community.